Salt-Tolerance in Castor Bean (Ricinus communis L.) Is Associated with Thicker Roots and Better Tissue K+/Na+ Distribution - Junlin Zheng; Gilang B. F. Suhono; Yinghao Li; Maggie Ying Jiang; Yinglong Chen; Kadambot H. M. Siddique (Agriculture, 2021)
Soil salinity is a serious threat to agriculture worldwide. Castor bean (Ricinus communis L.) is an in-demand oilseed crop containing 40–60% highly valued oil in its seeds. It is moderately sensitive to salinity. Two glasshouse experiments were conducted to assess plant growth and ion tissue distribution in different castor bean genotypes under various salt stress conditions to explore their potential for cultivation on saline land. Experiment 1 evaluated the response of five castor bean genotypes to four salt treatments (0, 50, 100, or 150 mM NaCl) up to 91 days after sowing (DAS). Experiment 2 further evaluated two genotypes selected from Experiment 1 in 1 m deep PVC tubes exposed to 0, 100, or 200 mM NaCl treatment for 112 DAS (Experiment 2). Experiment 1 showed that salt addition (particularly 150 mM NaCl) reduced plant height, stem diameter, shoot and root dry weights, photosynthetic traits, and leaf K+/Na+ ratio while increasing the leaf Na+ concentration of castor bean plants. Two genotypes, Zibo (Chinese variety) and Freo (Australian wild type), were more salt-tolerant than the other tested genotypes. In Experiment 2, salt-stressed Zibo flowered earlier than the control, while flowering time of Freo was not influenced by salt stress. The 200 mM NaCl treatment reduced the total root length and increased the average root diameter of both Zibo and Freo compared to the control. In addition, the 200 mM NaCl treatment significantly decreased total leaf area, chlorophyll content, and shoot and root dry weight of both castor bean genotypes by 50%, 10.6%, 53.1%, and 59.4%, respectively, relative to the control. In contrast, the 100 mM NaCl treatment did not significantly affect these traits, indicating that both genotypes tolerated salt stress up to 100 mM NaCl. In general, Freo had greater salt tolerance than Zibo, due to its higher average root diameter, lower Na+ concentration, and higher K+/Na+ ratio in young leaves under salt conditions. In conclusion, genotype Freo is recommended for cultivation in saline soils and could be used to breed high-yielding and salt-tolerant castor bean genotypes.